Environment and Breast Cancer - Russo, Jose.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Breast cancer is a complex disease caused by multiple environmental and lifestyle factors interacting with genetic susceptibility across the life span. Therefore, environmental factors are of intense interest to both researchers and community members, including women with breast cancer. There is not adequate literature that addresses this issue comprehensively from epidemiological, experimental, and translational research perspective. This book is aiming to fill this gap by gathering in 11 chapters the most recognized expert in the field of breast biology and cancer with special interests in environmental issues.
Epidemiologic basis of the role of environmental endocrine disruptors and breast cancer -- The windows of susceptibility and breast cancer risk -- The puberty as a window of risk for exposure to environmental agents and its effect in breast development -- Early life exposure Bisphenol A and breast Neoplasia -- Genomic changes induced by endocrine disruptors in the mammary gland -- Proteomic basis for the increase susceptibility of the mammary gland to carcinogenesis after prepubertal exposure to Bisphenol A -- Dioxin as an environmental pollutants and its role in breast cancer -- Effect of Exposure to Perfluorooctanoic Acid (PFOA) in the mammary Gland -- The effect of radiation in the mammary gland biology and cancer -- Diet as an environmental stressor in the mammary gland.
Keywords: Cancer research; Pharmacology; Cancer Research; Pharmacology/Toxicology.